ULTRASTRUCTURAL CHARACTERISTICS OF THE TESTICULAR CAPILLARIES IN THE DOG (CANIS-FAMILIARIS, L) - Duarte, H. E.; Deoliveira, C.; Orsi, A. M.; Vicentini, C. A. (Blackwell Wissenschafts Verlag Gmbh, 1995)
The main ultrastructural and cytophysiological characteristics observed on the testicular capillaries in the dog concern exocytosis and endocytosis processes, probably related to fluid and solute transport through the cells.